ANALISIS TAKTIK KOMUNIKASI ALDI’S BURGER DALAM PERSPEKTIF RONALD D. SMITH - Reza Pandi Tatwa; Mulharnetti Syas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Aldi’s Burger is a culinary business owned by Aldi Taher that successfully gained public attention through a viral communication strategy without heavily relying on paid advertising. This study aims to analyze the implementation of Aldi’s Burger communication tactics from the perspective of Ronald D. Smith’s Strategic Planning for Public Relations, particularly in the selection and integration of communication tactics. The research employed a qualitative descriptive approach using a case study method. Data were collected through social media observation, digital documentation, analysis of online media coverage, and relevant literature review. The findings reveal that shared media emerged as the dominant communication tactic through humorous and repetitive commenting activities on Threads and Instagram, which successfully triggered public awareness and audience engagement. Furthermore, interpersonal communication through word-of-mouth and influencer reviews strengthened the credibility and legitimacy of the brand. This viral phenomenon later evolved into earned media in the form of extensive coverage by national online media. Meanwhile, the minimal use of paid media indicates that Aldi’s Burger relied more on organic audience participation than advertising-based promotion. This communication strategy reflects the characteristics of contemporary digital communication that emphasize audience participation as a central element in message dissemination. The study confirms that the integration of shared media, interpersonal communication, earned media, and owned media can create a low-cost yet high-impact communication strategy. These findings reinforce Ronald D. Smith’s perspective that creative communication and tactical integration are key factors in successful public relations communication. Practically, this study demonstrates that culinary MSMEs can develop brand awareness and legitimacy through creative digital communication strategies without depending heavily on paid advertising.